If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -9(y + 5) = (y + -1) Reorder the terms: 12 + -9(5 + y) = (y + -1) 12 + (5 * -9 + y * -9) = (y + -1) 12 + (-45 + -9y) = (y + -1) Combine like terms: 12 + -45 = -33 -33 + -9y = (y + -1) Reorder the terms: -33 + -9y = (-1 + y) Remove parenthesis around (-1 + y) -33 + -9y = -1 + y Solving -33 + -9y = -1 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -33 + -9y + -1y = -1 + y + -1y Combine like terms: -9y + -1y = -10y -33 + -10y = -1 + y + -1y Combine like terms: y + -1y = 0 -33 + -10y = -1 + 0 -33 + -10y = -1 Add '33' to each side of the equation. -33 + 33 + -10y = -1 + 33 Combine like terms: -33 + 33 = 0 0 + -10y = -1 + 33 -10y = -1 + 33 Combine like terms: -1 + 33 = 32 -10y = 32 Divide each side by '-10'. y = -3.2 Simplifying y = -3.2
| -1.25x+3=0 | | 4x-6+52=9x+11 | | -1.25+3=0 | | 45=.25x | | -12x-33=9-6x | | lx+7l=3 | | 5p^2+8p-7=0 | | 180+1.5x+3x+x=455 | | 1-4p=1-3p | | 300+5*7= | | 400+4*7= | | 9x+13y=2 | | 6y-7-2y+2=0 | | 3v^2-17v+23=3 | | 9=.005x^2+.002x | | 5t^5+35t^2-20t=0 | | x+4/9=1/3 | | 3n^2+23n+42=2 | | 3n^2+23n+42=-2 | | 9=0.005x^2+0.002 | | .35x+.75(120+x)=.85(120) | | 6x-4(x+10)=-34 | | -8h+4=7-5h | | 3x-5=10+7(10-2x) | | 3b^2+20b+4=-8 | | (v+1)(v+3)=15 | | 2x^2+6x-22=0 | | d+0.002d=510 | | 8=3(.5-4)+8 | | -3x+3.6=-4x+5.4 | | -2y=4y | | 7d=-2d |